2014
DOI: 10.1371/journal.pone.0098519
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of DENV-2 Asian-American Genotype Lineages in the Americas

Abstract: The Asian/American (AS/AM) genotype of dengue virus type 2 (DENV-2) has been evolving in the Americas over the last 30 years, leading to several waves of dengue epidemics and to the emergence of different viral lineages in the region. In this study, we investigate the spatiotemporal dissemination pattern of the DENV-2 lineages at a regional level. We applied phylogenetic and phylogeographic analytical methods to a comprehensive data set of 582 DENV-2 E gene sequences of the AS/AM genotype isolated from 29 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 44 publications
6
37
0
Order By: Relevance
“…The strains belonging to the AA3 lineage are found to be isolated from the Caribbean region (such as Puerto Rico and Jamaica) and Brazil. This observation was supported by the earlier studies wherein Caribbean islands have been reported to be the main source of DENV-2 viruses in Brazil and northeastern Brazil appears to be an important route of introduction and dissemination of this virus in SAM region (Figueiredo et al, 2014; Mir et al, 2014). Furthermore, gene flow via islands has been proposed to be a cause of spread to other countries in the Americas (Allicock et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…The strains belonging to the AA3 lineage are found to be isolated from the Caribbean region (such as Puerto Rico and Jamaica) and Brazil. This observation was supported by the earlier studies wherein Caribbean islands have been reported to be the main source of DENV-2 viruses in Brazil and northeastern Brazil appears to be an important route of introduction and dissemination of this virus in SAM region (Figueiredo et al, 2014; Mir et al, 2014). Furthermore, gene flow via islands has been proposed to be a cause of spread to other countries in the Americas (Allicock et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…In spite of this, continuous surveillance of the virus can facilitate the early detection of novel emerging variants, and acts as a fundamental part of integrated preventive strategy. Previous studies were mainly about specific country and region730313233, or only focused on certain genotype19. Therefore, the challenge is to analyze evolutionary history and geographic spread of the virus globally.…”
Section: Discussionmentioning
confidence: 99%
“…While Mir et al 33. investigated DENV-2 migration using similar tools, the study was geographically limited to the Americas including the Caribbean.…”
Section: Discussionmentioning
confidence: 99%
“…DENV-2 has six genotypes, consisting of Asian I, Asian II, Southeast Asian/American, Cosmopolitan, American and sylvatic Cruz et al, 2013;Mir et al, 2014). Additionally, DENV-3 can be arranged into five genotypes, including I-V. DENV-4 is classified into four genotypes, consisting of I-III and the sylvatic genotype.…”
Section: Introductionmentioning
confidence: 99%